Lipase-catalyzed Solvent-free Synthesis of Polyglycerol 10 (PG-10) Esters - Satyawali, Yamini; Cawenberghs, Lieve; Dejonghe, Winnie (Chemical and Biochemical Engineering Quarterly, 2020)
Polyglycerol fatty acid esters, which have been widely used as emulsifiers in food, medicine and cosmetics industries, were the subject of solvent-free enzymatic synthesis in this study. There have been previous reports on enzymatic synthesis of various polyglycerol esters; however, this investigation extends the synthesis to PG-10 esters. The effects of substrate molar ratio, addition of emulsifiers to enhance mixing, and addition of molecular sieves or N2 flushing for water removal, was investigated. The solvent-free synthesis using N2 flushing leads to complete conversion of fatty acid, yielding a completely acid free product. The synthesis is validated for polyglycerol laurate and polyglycerol caprylate, both useful products in the cosmetic industry.